2013
DOI: 10.1097/psy.0b013e3182826881
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Orientation and Disclosure in Relation to Psychiatric Symptoms, Diurnal Cortisol, and Allostatic Load

Abstract: LGBs did not manifest more stress-related problems than did heterosexuals. Life transitions like disclosing to one's family and friends may be protective against psychopathologies and hyperactive cortisol awakening responses. Our novel findings underline the roles disclosure processes have on positive health and well-being for sexual minorities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
125
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(137 citation statements)
references
References 70 publications
9
125
2
1
Order By: Relevance
“…It may also be the case that more resilient and less anxious individuals are more likely to come out. In one recent study including biological markers, disclosed gay men evidenced fewer self-reported psychiatric symptoms and lower awakening cortisol levels than non-disclosed gay men (Juster et al, 2013), though findings from another study showed that gay men who were more out at work suffered greater levels of negative affect and higher levels of diurnal cortisol (Huebner & Davis, 2005). Inthis study,changesinpre-topost-socialstresslevelsofcortisol did not differ between homosexual and heterosexual men nor did they vary according to gender typicality.…”
Section: Discussionmentioning
confidence: 93%
“…It may also be the case that more resilient and less anxious individuals are more likely to come out. In one recent study including biological markers, disclosed gay men evidenced fewer self-reported psychiatric symptoms and lower awakening cortisol levels than non-disclosed gay men (Juster et al, 2013), though findings from another study showed that gay men who were more out at work suffered greater levels of negative affect and higher levels of diurnal cortisol (Huebner & Davis, 2005). Inthis study,changesinpre-topost-socialstresslevelsofcortisol did not differ between homosexual and heterosexual men nor did they vary according to gender typicality.…”
Section: Discussionmentioning
confidence: 93%
“…There is supporting evidence for the novel finding of reduced prevalence of depression in gay men compared to heterosexual men and no difference in prevalence between heterosexual and bisexual men reported in a US population sample and in another recent Canadian study. 14,20 The findings reported in the Canadian study were based on a small convenience sample recruited in one location, and thus the lower prevalence of depression found may not be generalizable to the population. 14 Although lower prevalence for gay men was not repeated here, there was no significant difference found in MDE prevalence for sexual minority men compared to heterosexual men.…”
Section: Discussionmentioning
confidence: 99%
“…14,20 The findings reported in the Canadian study were based on a small convenience sample recruited in one location, and thus the lower prevalence of depression found may not be generalizable to the population. 14 Although lower prevalence for gay men was not repeated here, there was no significant difference found in MDE prevalence for sexual minority men compared to heterosexual men. With only self-identity as a measure of sexual orientation, it is not possible to determine the effect of discordance between sexual identity and sexual activity or attraction in this study to compare to findings, previously reported in Scott et al 20 and the California Quality of Life study (CQoL), 21 that heterosexually identified men with same-sex partners account for higher prevalence of depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If androphilia aligns with a sneak copulation strategy in men, for example, a culture celebrating conspicuous gay pride and abstinence from heterosexual contact, while cautioning against the dishonesty of bisexuals and unidentified nonheterosexuals, would effectively disarm potential sneak copulators. The homosexual identity may act as a reputational passport, with the relief and psychological benefits of coming out (Juster et al 2013) coinciding with an escape from the obscurity and intolerance of mere nonheterosexuality, into a welcoming community of sexual refugees who promote identification and solidarity. It would not be controversial to suggest that the LGBTQ community established itself in response to the homophobic forces that perpetrate violence and discrimination against nonheterosexuals (Beachy 2014).…”
Section: Identity and Exclusivitymentioning
confidence: 98%